Assessment of muscle mass, risk of falls and fear of falling in elderly people with diabetic neuropathy - Hudson Azevedo Pinheiro; Karla Helena Coelho Vilaça; Gustavo de Azevedo Carvalho
Abstract Objective : To assess muscle mass, risk of falls and fear of falling in elderly adults with diabetic neuropathy (DNP). Methods : 50 elderly patients with diabetes mellitus (DM) and diabetic neuropathy (NPD) participated in this study. Risk of falling was assessed using the Berg Balance Scale (BBS). Fear of falling was assessed by means of the Falls Efficacy Scale-International (FES-I). Muscle mass was assessed by tetrapolar bioimpedance analysis (BIA) and Janssen's equation. Subjects were divided into two groups: one with a history of falls in the six months before study enrollment (G1) and the other without history of falls (G2). Results : There were statistically significant differences between G1 and G2 regarding lean body mass (p < 0.05), risk of falls as measured by the BBS (p < 0.01), and fear of falling as measured by the FES-I (p < 0.01). In addition, there was a significant correlation between the BBS and BIA (r = 0.45 and p < 0.01), showing that the greater the lean body mass, the lower the risk of falling. Conclusions : We found an association between lean mass, risk of falls and fear of falling in elderly adults with DNP and a history of falls from own height.